Response of broiler chickens Gallus gallus domesticus to dietary supplementation with LAB-treated sorghum seed - Alban Mugoti; Chikumba Nation; Munengwa Anderson (Syiah Kuala University, 2022)
In recent years, livestock production has been heavily affected due to the effects of climate change with shortages in feed being recorded. A study was conducted to determine the effect of fermented Sorghum bicolor grain on the growth of broiler chickens. The study aimed to utilize available feed resources without compromising on animal productivity and health. A total of 160 day-old Cobb broiler chicks were used which were randomly allocated to four dietary treatments of 10 birds for each treatment. The treatments were replicated four times. Different levels of ground, LAB-treated sorghum were analyzed on growth performance, feed intake, and feed conversion ratio (FCR), carcass, and organ weights. The diets were each formulated as T1, T2, T3, and T4 for 25%, 50%, 75%, and 0% LAB-treated sorghum inclusions respectively. T4 was the control. The remaining percentage was filled with general feed which is the commercially available feed. The results revealed that growth performance and FCR of the broilers on T1 were similar to those of the control diet but interestingly superior (P0.05) to T2 and T3-fed birds. Birds fed on T3 had a low feed intake (p0.05) as compared to other treatment diets. Mortality was depressed (p0.05) in T1 as compared to T2, T3, and T4 respectively but was significantly (p0.05) similar between T4 (control) and T2. Live weight of birds with 25% sorghum inclusion compared favorably with the control (T4) (P0.05) as was the carcass and percentage dressed weights. Internal organ weights (liver, gizzard, and heart) of the 3 treatments (T1, T2, and T4) were significantly (p0.05) lower than that of birds under T2 (50% sorghum inclusion). It was concluded that the inclusion of 25% LAB-treated sorghum in broiler rations brought about a better performance than 0%, 50%, and 75% LAB-treated sorghum inclusion levels.